2011
DOI: 10.1098/rspa.2011.0212
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of retained austenite in bainitic steel: an  in situ study

Abstract: The tempering of two-phase mixtures of bainitic ferrite and carbon-enriched retained austenite has been investigated in an effort to separate the reactions that occur at elevated temperatures from any transformation during cooling to ambient conditions. It is demonstrated using synchrotron X-radiation measurements that the residue of austenite left at the tempering temperature partly decomposes by martensitic transformation when the sample is cooled. It is well established in the published literature that film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 29 publications
5
54
0
Order By: Relevance
“…The reduction in lattice parameter (a γ ) occurs as the austenite decomposes. The reduction in lattice parameter at constant temperature implies that carbon leaves solid solution within the austenite [18,19]. Since thermodynamics precludes the possibility that carbon will leave austenite and enter solid solution in the ferrite, then the only possibility is that the carbon precipitates as carbides.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in lattice parameter (a γ ) occurs as the austenite decomposes. The reduction in lattice parameter at constant temperature implies that carbon leaves solid solution within the austenite [18,19]. Since thermodynamics precludes the possibility that carbon will leave austenite and enter solid solution in the ferrite, then the only possibility is that the carbon precipitates as carbides.…”
Section: Resultsmentioning
confidence: 99%
“…They showed that these tiny austenite precipitates inhibited cleavage fracture and led to a lowering of the ductile-brittle transition temperature [78]. Podder et al [79] found thin layers of austenite in Fe-C-Ni-Si steel to be more stable against martensitic transformation than blocky austenite. Yuan et al [68] made similar observations on nanoscale austenite layers in Fe-Cr-C martensite steels.…”
Section: Segregation-induced Nanoscale Martensite To Austenite Reversmentioning
confidence: 97%
“…During tempering (heat treatment below the austenite phase field) the steel approaches the equilibrium mixture of ferrite and cementite, usually by a reconstructive process. The power of in-situ synchrotron X-ray diffraction to shed new light was recently shown in the study of the decomposition of retained austenite in Fe-0.39C-4.09Ni-2Si wt% bainitic steel when using a combination of microscopy, laboratory X-ray diffraction and in-situ synchrotron X-ray experiments [10,11], it was demonstrated that after tempering at 400…”
mentioning
confidence: 99%
“…After formation of a bulk nanoscale bainitic microstructure, the retained austenite is unable to accommodate all the carbon that is rejected from the ferrite [6]. The carbon enrichment of retained austenite is first controlled by diffusion in ferrite, but is subsequently limited by diffusion in austenite [10]. During continuous heating, austenite was not enriched by carbon from supersaturated ferrite.…”
mentioning
confidence: 99%